Etika Muamalah dalam Al-Qur’an dan Relevansinya bagi Penguatan Ekonomi Warga Muhammadiyah - Miasari; Miftahul Jannah; Aimatul Khoiriyah; Hera Hapsari Kusuma; Heri Rifhan Halili (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
The ethics of muamalah is one of the fundamental pillars in the teachings of the Qur'an that regulates the economic, social, and moral relations of Muslims. In the modern context, global economic challenges, exploitative economic practices, and weakening social solidarity demand the actualization of the values ​​of muamalah ethics as a foundation for strengthening the economy of the community, including within the Muhammadiyah community. This article aims to analyze the concept of muamalah ethics in the Qur'an and its relevance in strengthening the economy of Muhammadiyah members in a sustainable manner. This study uses a qualitative approach with a library research method, accompanied by content analysis of the verses of the Qur'an related to muamalah, classical and contemporary interpretations, and scientific literature on Islamic economics and the Muhammadiyah economic movement. The results of the study indicate that the main principles of the ethics of muamalah in the Qur'an such as justice (al-'adl), honesty (al-shidq), trustworthiness, the prohibition of usury, gharar, and exploitation, as well as encouragement of productive work and equitable distribution have strategic relevance in building the economic independence of Muhammadiyah members. Implementing these values ​​can strengthen an entrepreneurial ethos, increase social trust, and build an inclusive and equitable community economic system. Theoretically, this article contributes to the development of contextual Islamic economic ethics studies, while practically providing a normative framework for strengthening the economy of Muhammadiyah members based on Qur'anic values.